Case Report: Synchronous Removal and Implantation of Peritoneal Dialysis Catheter Using Bilateral Transversus Abdominis Plane Block - Jakšić, Ante; Vujičić, Božidar; Deša, Diana; Gršković, Antun; Vukelić, Ivan; Španjol, Josip; Rački, Sanjin; Markić, Dean (Frontiers in Medicine, 2022)
Background: Peritoneal dialysis (PD) surgery include PD catheter insertion and removal. Both procedures require the use of anaesthesia. Since, the end-stage renal disease (ESRD) patients usually has severe comorbidities and general anaesthesia could be risky for this patient anaesthesia methods without systemic effect are required. Transversus abdominis plane (TAP) block as a newer method of regional anaesthesia is technique without systemic effect and recently started to be used in ESRD patients for PD catheter placement and/or removal. Here we report a patient in whom we for the first time simultaneously removed and implanted a PD catheter by using a bilateral transversus abdominis plane block. Case Presentation: The patient was a 80-year-old man who was admitted for removal of malfunctioned PD catheter. Since patient opted for staying on PD simultaneous implantation of catheter was planned. Because of his age and significant comorbidities general anaesthesia was avoided and bilateral TAP block become our option. In the same anaesthesia, using bilateral TAP block, old PD catheter was removed and new one was implanted. Until now the patient is on regular PD without any complications. Conclusions: The TAP block is safe an efficient method and could be used as primary anaesthetic technique in ESRD patients for PD surgery even for synchronous removal and implantation of PD catheter.